A Nosocomial Cluster of Roseomonas mucosa Bacteremia Possibly Linked to Contaminated Hospital Environment. (October 2020) - Okamoto, Koh; Ayibieke, Alafate; Saito, Ryoichi; Magara, Yuki; Ogura, Kenichi; Ueda, Reiko; Ogawa, Hina; Hatakeyama, Shuji
Abstract : Background: The genus Roseomonas, containing pink-pigmented glucose nonfermentative bacteria, has been associated with various primary and nosocomial human infections; however, to our knowledge, its nosocomial transmission has never been reported in the literature. Here, we report a nosocomial cluster of Roseomonas mucosa bacteremia. Methods: Two cases of R. mucosa bacteremia in 2018 are described. Clinical and epidemiological investigations were undertaken. Environmental surfaces prone to water contamination in the patient wards were sampled and cultured. The sampled surfaces included sinks, faucets, toilets, sewage, showerheads, refrigerators, exhaust vents, and washing machines. The 2 clinical isolates and all environmental isolates that showed growth of pink colonies were identified using matrix-assisted laser desorption/ionization time of flight mass spectrometry and 16S rRNA gene sequencing. Pulse-field gel electrophoresis (PFGE) was performed and fingerprinting software was used to analyze the DNA restriction patterns and determine their similarity. Results: Two patients who developed R. mucosa bacteremia had received care from the same treatment team. The patients were on different wards but had overlapping hospital stays. In addition to the treatment team, no other shared exposure was identified. Moreover, 126 environmental surfaces were sampled, of which 7 samples grew pink colonies. The 9 isolates from the patients and the environmental samples were examined using 16S rRNA gene sequencing. Overall, 7 isolates, including isolates from both patients, were identified as R. mucosa, and the other 2 isolates were identified as Roseomonas gilardii subsp. rosea (Fig. 1). With 80% similarity as a cutoff, PFGE analysis revealed that the R. mucosa isolates from 2 patients' blood cultures and 3 environmental isolates (a washing machine in the ward, a sink in the shared washroom, and a sink in the patient room) belonged to the same clone (Fig. 2). Conclusions: The hospital water environment was contaminated with R. mucosa, and the same clone caused bacteremia in 2 separate patients, suggesting nosocomial transmission of R. mucosa possibly linked to contaminated water, environment, and/or patient care. Funding: None Disclosures: None